Rheological characterization of sugar solutions for the evaporation-crystallization process - Gómez, A Martinez; Bazán, I Sánchez; Osorio-Mirón, A; Zamora, L López; Sánchez Bazán, LA; Aguilar, E Hernández Aguilar (Nexo Revista Científica, 2011)
In this work, an experimental study for the rheological characterisation of sugar solutions in the process of sugar production was performed. The main purpose was the characterisation of sugar solutions in order to model its rheological behaviour for optimising the evaporation-crystallisation process at a later stage. In the experiments, a 3k factorial design of experiment was used, where it considers the interaction of three factors in determining the response variable, in this case the factors are: the concentration (°Bx), the temperature and revolutions per minute (shear rate), each one with three levels, taking as response variable viscosity. The experimental development and analysis of results lead to the determination of the rheological model for the test solutions in the study range of the factors of interest, and it is proposed a type Ostwald-de Waele model for dilatant fluids. Keywords: Rheological model; Shear rate; Viscosity DOI: http://dx.doi.org/10.5377/nexo.v24i1.595 Nexo, Vol. 24, No. 1, pp. 61-71, 2011